Challenges faced by SMME's during Covid-19 pandemic in Mangaung Metro Municipality - Moipolai, Letshego Merriam (University of the Free State, 2022)
Small, medium, and micro-enterprises (SMMEs) are important economic drivers in South Africa. SME's account for 95% of all businesses worldwide and contribute 40% of all economic activity. South Africa's small businesses are a major source of job creation. The COVID-19 Pandemic, also known as Coronavirus, has had a significant impact on business operations as well as customer activities and trends. Because of the virus's rapid spread, the Pandemic has had immediate socioeconomic consequences in both developed and growing countries and is now the new normal. The study aims to investigate and identify challenges faced by SMME during the COVID-19 pandemic in the Mangaung Metro Municipality, the effects it has on business development, and identifying possible solutions to these challenges. This study was executed using a qualitative approach. Purposive sampling was used, which allows participants to be chosen solely on the essential characteristics that make them the holders of the data needed for the study. A sample size of 20 SMMEs within Mangaung municipality was used. This sample included representatives from Bloemfontein, Thaba-Nchu, and Botshabelo. Open-ended questions were used in conjunction with other interviewing techniques to delve deeply into topics, allowing participants to elaborate and express their views freely. Qualitative interviews were based primarily on patterns and recognising the point of data saturation. South Africa's SMMEs were faced with many challenges during the COVID-19 pandemic, these challenges include but not limited to lack of access to funding, limited access to local and international markets, strict Legislations and regulations, lack of training and education and access to technology. Themes and interpretive analysis were performed. The inability to obtain financing was identified is one of the main challenges that SMMEs in Mangaung Metro Municipality face. This severely impedes the development and expansion of these businesses. To survive in this region, SMMEs must acknowledge the importance of trying to access markets locally and internationally, as well as have the necessary skills and resources while pursuing government support. Perception and sample size were two of the limitations, and recommendations includes increased market accessibility, skills development, access to proper infrastructure, and technology advancement in SMME development. Future research may investigate the challenges that SMMEs may face if these findings are not addressed in future.
Dissertation (MBA (Business Administration))--University of the Free State, 2022